Can dietary aromatic amino acid supplementation be beneficial during fish metamorphosis? - Pinto, W. (2014)
Aromatic amino acids (AA, phenylalanine and tyrosine) are the precursors of thyroid hormones, which regulate metamorphosis in all vertebrates. In fish, this is a critical developmental stage where physiological requirements for aromatic AA may increase. Therefore, it is possible that dietary aromatic AA supplementation may be beneficial to accomplish a successful transition from larvae to the juvenile stage. This work aimed to assess the effect of dietary aromatic AA supplementation on tyrosine metabolism in species with an accentuated (Senegalese sole, Solea senegalensis) and a less marked (gilthead seabream, Sparus aurata) metamorphosis. For this purpose, either species were fed Artemia and subsequently received or not an aromatic AA supplement through tube-feeding, together with a L-[U-14C] tyrosine marker, throughout metamorphosis. Tyrosine was elected as a tracer since the metabolic fate of this aromatic AA is directly linked to the production of thyroid hormones and metamorphosis. Results showed that dietary phenylalanine supplementation did not increase tyrosine retention in Senegalese sole larvae during metamorphosis, suggesting that this species may not be able to biosynthesise tyrosine from phenylalanine at a sufficient rate to supply its physiological requirements until after metamorphosis. Furthermore, dietary tyrosine supplementation effectively increased tyrosine availability in Senegalese sole body fluids at metamorphosis, most likely for coping with metamorphosis-related processes, such as production of thyroid hormones. Therefore, dietary tyrosine supplementation may be beneficial for Senegalese sole during metamorphosis. On the other hand, results indicated that gilthead seabream larvae do not seem to require an additional supply of aromatic AA during metamorphosis, probably because the physiological requirements for tyrosine do not increase during this developmental stage. The different results observed for Senegalese sole and gilthead seabream are probably related to the complexity of metamorphosis that each species undergoes and to the needs for production of thyroid hormones, which seems to affect aromatic AA requirements during this critical stage of development. These findings may be important for physiologists, fish nutritionists and for the flatfish aquaculture industry.